Tim's Vermeer [videorecording (DVD)] - Jillette, Penn (Sony Pictures Classics, 2014)
Tim Jenison, a Texas-based inventor, attempts to solve one of the greatest mysteries in all art: How did seventeenth century Dutch Master Johannes Vermeer manage to paint so photo-realistically, 150 years before the invention of photography? Spanning ten years, his adventure takes him to Delft, Holland, where Vermeer painted his masterpieces, to the north coast of Yorkshire to meet artist David Hockney, and even to Buckingham Palace to see a Vermeer masterpiece in the collection of the Queen.